Asynchronous event-triggered H... control problem for two-time-scale systems based on double-rate sampled-data. Issue 16 (November 2022) - Yan, Yifang; Yang, Chunyu; Ma, Lei; Zhou, Linna
Abstract: This work focuses on the asynchronous event-triggered H ∞ control problem for two-time-scale systems (TTSSs) with double-rate sampling. Firstly, by fully considering the positive exponential items and the quadratic items including the state information, an improved triggering condition is constructed. Based on the improved condition, an asynchronous event-triggered mechanism (ETM) is derived, which realizes the independent update on the triggering signals of the fast and slow subsystems. Secondly, an asynchronous event-triggered control scheme is established by co-designing the H ∞ controller and the asynchronous ETM. The designed asynchronous control scheme mainly has two features: 1) reducing the frequency of signal transmission at the whole stage of system operation; 2) being applied to the TTSSs with double-rate sampled-data. Finally, examples are presented to demonstrate the validity and merits of the obtained methods.